THE ROLE OF COUNSELING TEACHERS BASED ON THE CURRICULUM FREEDOM TO LEARN - Elfira, Yenni; Mudjiran, Mudjiran; Nirwana, Herman; Karneli, Yeni (Universitas Trunojoyo Madura, 2022)
This paper aims to determine the role of guidance and counseling teachers based on the “Merdeka Belajar” curriculum. This writing uses a qualitative research method which is a literature study. The concept of the curriculum